Revisiting Utricularia section Nigrescentes (Lentibulariaceae) in India and re-instating Utricularia roseopurpurea, integrating morphological and molecular data - Krishnapriya, M. P.; Silva, S. R. [UNESP]; Miranda, V. F.O. [UNESP]; Nampy, S. (Indian Association for Angiosperm Taxonomy (IAAT), 2024)
Utricularia L. section Nigrescentes (Oliv.) Komiya (Lentibulariaceae), distributed in tropical Africa, Madagascar, Asia to Japan and Australia includes four species, U. bracteata R.D.Good, U. caerulea L., U. roseopurpurea Stapf ex Gamble and U. warburgii K.I.Goebel. Utricularia caerulea and U. roseopurpurea occur in India, and the latter species has long been treated as a synonym of the former. The identity of U. roseopurpurea has been confirmed using morphological, micromorphological, and molecular data and the species has been re-established. Multiple accessions of the species included in the phylogenetic study formed a sister clade to U. caerulea with strong branch support. The section Nigrescentes in India is revisited, and the distribution of both species is defined based on extensive field and herbarium surveys. The affinities between the two species are discussed. Full descriptions, notes on habitat requirements, nomenclature, assessment of the conservation status and photographs are provided for both species.
Keywords: Carnivorous plants; nrITS; Taxonomy; Utricularia caerulea; Western Ghats